Mistreatment: the suffering body of the ‘indians’ facing the eyes and ears of the King - Araya, Alejandra (Universidad de Chile. Facultad de Filosofía y Humanidades, 2017)
This paper explores the concept of “mistreatment” as part of the problem of the “body” within the colonial domination process. The building of an image of the other, from the rhetorical configuration of an injured, damaged and endangered body, presents –in the texts of Fray Bartolomé de las Casas– fundamental discourses that would replicate above the entire colonial domination process and the governing of the body of the other, articulating a theory about the “conquests” as a form of tyranny, and the building of a policy of denouncing injustice from the exhibition of the damaged body as its proof. The body of the Indians builds, as a result, a new subjectivity about human condition, and at the same time it gave these bodies a presence as body of crime in front the eyes and ears of the King, confronting his own conscience.